The metabolism of selected organic compounds by microorganisms in the Athabasca River ... - Westlake, D. W. S.; Coutts, R. T.; Nix, P. G.; Pasutto, F. M. (University of Alberta Library, 1981)
In this study, the ability of microorganisms to degrade selected organic substrates in samples of Athabasca River water and water-sediment has been determined. Analysis of laboratory-incubated samples using gas chromatography/ mass spectrometry has shown that trace amounts (100 µg/L) of m-cresol and camphor can be quantified and a \"50% depletion time\" determined. Sites both above the oil sands region and downstream from the area of mining activity had a noticeably high level of activity regarding the degradation of these compounds. In addition, the incubation of samples taken along a transect of the river just downstream from the oil sands plants showed higher rates of microbial degradation on the west bank where effluents and drainage would likely be concentrated. Other substrates, 2,6-xylenol and methylsalicylate, were not suitable for degradation studies due to depletion caused by non-biological processes. Analysis of 14C-labelled substrates indicated that \"natural\" compounds (amino acids and starch) ...